ANALISIS KEMAMPUAN MENULIS ARTIKEL ILMIAH MAHASISWA PERTANAHAN - Irianti, Nathasa Pramudita; Nurasiah, Lilis (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to analyze the scientific article writing skills of students at the National Land University. The ability to write scientific articles’s considered important because students are required to be able to express ideas and research findings in a structured, critical, and logical manner. This study adopted quantitative approach with descriptive design. Data were obtained from 51 scientific article assignments of first year students who had completed the Indonesian Language and Writing courses in the Odd Semester of the 2024/2025. The research instrument includes a scientific writing ability assessment rubric, with indicators such as creativity in developing content, use of relevant and credible references, and delivery of knowledge clearly and easily understood. The assessment criteria for the ability to write scientific articles refer to the modified guidelines from Topen which classifies the assessment scores for scientific articles into four groups, namely very good, good, sufficient, and less. The majority of students are at a good level (64.7%) in the creativity of content development, in the ability to use relevant and credible references, the majority of students are also in the good category (52.94%). In the category of conveying knowledge clearly and easily understood, the majority of students also received a good assessment (60.78%). Based on the analysis of students' scientific articles assessed from three main aspects, the students' ability to write scientific articles is classified as good, although in some parts improvements and development are still needed to be even better.